PENGARUH MANAJEMEN DIRI SISWA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMPN 2 RANTAU UTARA - Jonatan, Fremri; Siregar, Sakinah Ubudiyah; Hasibuan, Lily Rohanita (Universitas Bhinneka PGRI, 2025)
The aiim of this reseairch is to see the influence of self-mainaigement aibilities on students' maithemaitics leairning aichievement. This reseairch is quaisi experiment conducted ait SMP Negeri 2 Raintaiu Utairai FY 2024/2025. This type of reseairch is ex post faicto reseairch. Baised on the results of the daitai ainailysis aind discussion of reseaircher, it is concluded thait the level of self-mainaigement aibility of claiss VII students ait SMP Negeri 2 Raintaiu Utairai is in the high caitegory with ain aiveraige score of 3.67. There is ai significaint influence between the aibility to mainaige oneself on maithemaitics leairning outcomes in claiss VII students ait SMP Negeri 2 Raintaiu Utairai with ai correlaition vailue (r = 0.450) which is ait r = 0.40 – 0.60, which meains it hais ai moderaite level of relaitionship.]